Introduction. On the banality of mobilisation in Africa - (:unkn) unknown (My University, 2015)
This work comprises case studies (12) representing as many specific situations in Africa. We consider them to be neither exceptional nor inconceivable within the general framework of social sciences. Our approach is that Africa, far from being a 'cultural sphere', forms an area of empirical scientifi analysis and a specific point of insertion into the world economy. Africa is a tool like any other for considering generalities and for improving our understanding of realities that are very different and yet follow the same broad tendencies.
Keywords: African Research